Ekstraksi Kalium dari Sabut Kelapa Menggunakan Metode Microwave-Assisted Extraction - Setyabudi, Lintang Sekar Wulandari; Yasiroh, Halin Hijra; Nove Kartika Erliyanti; Soemargono (Jurnal Ilmiah Teknik Kimia, 2024)
Coconut husk is a byproduct of coconut production that takes a considerable amount of time to degrade, potentially causing environmental pollution. Coconut husk contains various minerals, with potassium being one of the highest. This research aims to determine the effect of the optimum solvent-material ratio, extraction time, and microwave power on potassium content and yield as well as the degree of acidity (pH) of coconut fiber extract. Potassium from coconut husk was extracted using microwave-assisted extraction. The microwave power used in this research was 450 watts and 600 watts with extraction times varying from 50 to 130 minutes and the ratio of raw materials and solvent in the form of distilled water (w/v) 1:3; 1:4; 1:5; 1:6; and 1:7. The best extraction results were obtained under the operating conditions of 600 watts power, 50 minutes extraction time, and 1:7 (w/v) ratio, with yields and potassium content of 99.8280% and 0.1021%. The highest pH value was obtained at 600 watts, 130 min, and material-to-solvent ratios 1:6 (w/v), measuring 9.2.